The Effectiveness of Using List Group Label Strategy Students’ on Vocabulary Achievement - Dian Tri Rahmi (Journal of English Language and Education, 2021)
This research was due to discovering the effectiveness of using list group label strategy on students’ vocabulary achievement at the second grade of SMPN 8 Bukittinggi in academic year 2019-2020. This research was caused by the lacked of students’’ vocabulary mastery in learning English at the second grade of SMPN 8 Bukittinggi. It can be proven by seeing the students’ laziness to bring a dictionary in English subject. It also impact to their interest in learning English. Other problems, the students were also difficult to differentiate between words; verbs, nouns, and adjectives in learning English. The students’ scores were under the minimum standard, 75. Hence, the researchers saw that LGL Strategy was due to discovering the effectiveness of using list group label strategy students’ on vocabulary achievement at the second grade of SMPN 8 Bukittinggi in academic year 2019-2020. This research was descriptive quantitative research. The population of the research was second grade students of SMPN 8 Bukittinggi consist of four classes. The sample was VIII.1 and VIII.2. To determine the sample, the researcher used a purposive sampling technique. The data was got through the documents’ vocabulary test before giving test, the test has been validated English lecturer and English teacher. The result was obtained by analyzing the data from students’’ vocabulary achievement from the result of the test. The finding showed that the effectiveness of the List group label strategy on students’ vocabulary achievement at the second grade of SMPN 8 Bukittinggi in Academic Year 2019-2020 with the score percentage 73.31 was effective. To sum up, the used List group label strategy on students’ vocabulary achievement in the second grade of SMPN 8 Bukittinggi in Academic Year 2019-2020 was effective